2022
DOI: 10.54905/disssi/v26i120/ms54e1998
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards child abuse among the general population in Saudi Arabia

Abstract: Background: Child abuse encompasses a wide range of physical, emotional, and sexual abuse, as well as negligence in child care, all of which can have a severe impact on a child's health and development. The purpose of this study is to assess the population's knowledge, attitudes, and behaviours about child abuse in Saudi Arabia. Methodology: This is a cross-sectional study conducted in Saudi Arabia between July and August 2021. This study covers the general population of Saudi Arabia. Online self-completed que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…In our study, gender, age, marital status, and monthly income did not exhibit statistically significant associations with knowledge or attitude scores. In contrary to our findings, a recent Saudi study found that the total knowledge score was significantly affected by age and gender (P<0.001 and P=0.04, in order), but not when being exposed to nasal bleeding [18]. Also, gender and marital status were significantly affecting the total knowledge, attitude, and practice scores among Saudi general population (P=0.001 and 0.029, in order) [19].…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, gender, age, marital status, and monthly income did not exhibit statistically significant associations with knowledge or attitude scores. In contrary to our findings, a recent Saudi study found that the total knowledge score was significantly affected by age and gender (P<0.001 and P=0.04, in order), but not when being exposed to nasal bleeding [18]. Also, gender and marital status were significantly affecting the total knowledge, attitude, and practice scores among Saudi general population (P=0.001 and 0.029, in order) [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Yassir et al discovered that of the 403 respondents in their study, 33.3% had good knowledge of its management [23]. Omar et al established that the overall total knowledge score was good among the population in KSA [24]. Saeed et al found that knowledge and awareness of epistaxis in the general population was generally good at 78% correctness regarding responses to the questionnaire [25].…”
Section: Discussionmentioning
confidence: 95%